URGENSI PENGUATAN KEMAMPUAN INTELIJEN DETEKSI DINI POLDA BABEL GUNA MENCEGAH BERKEMBANGNYA PAHAM RADIKALISME - Rahmat Robuwan (JURNAL AKTA YUDISIA, 2023)
AbstractThis research is entitled "The Urgency of Strengthening Intelligence Capabilities for Early Detection of the Babel Regional Police to Prevent the Development of Radicalism". This research is motivated by the increasing threat of violent extremism that leads to terrorism in Indonesia, which has created a vulnerable condition that threatens the right to feel safe and the stability of national security. In efforts to prevent and overcome violence-based extremism that leads to terrorism, a comprehensive strategy is needed to ensure systematic, planned and integrated steps involving the active role of all stakeholders. The problem raised in this paper is how to implement legal policies in an effort to strengthen the intelligence capabilities of the Bangka Belitung Regional Police's common sense in order to prevent the development of radicalism? What are the efforts to strengthen the early detection intelligence capabilities of the Bangka Belitung Regional Police in order to prevent the development of radicalism? This research method uses an empirical juridical approach. The results in this study include that it is still not optimal, both the application of laws and regulations related to the prevention and eradication of radicalism as well as the ability to detect early Sie Tekintel Dit Intelkam Polda Kep. Bangka Belitung to Prevent the Development of Radicalism.Keywords: Strengthening , Intelligence, Radicalism